Alert dwell time: introduction of a measure to evaluate interruptive clinical decision support alerts. (24th October 2015) - McDaniel, Robert B; Burlison, Jonathan D; Baker, Donald K; Hasan, Murad; Robertson, Jennifer; Hartford, Christine; Howard, Scott C; Sablauer, Andras; Hoffman, James M
Abstract: Metrics for evaluating interruptive prescribing alerts have many limitations. Additional methods are needed to identify opportunities to improve alerting systems and prevent alert fatigue. In this study, the authors determined whether alert dwell time—the time elapsed from when an interruptive alert is generated to when it is dismissed—could be calculated by using historical alert data from log files. Drug–drug interaction (DDI) alerts from 3 years of electronic health record data were queried. Alert dwell time was calculated for 25, 965 alerts, including 777 unique DDIs. The median alert dwell time was 8 s (range, 1–4913 s). Resident physicians had longer median alert dwell times than other prescribers ( P < .001). The 10 most frequent DDI alerts ( n = 8759 alerts) had shorter median dwell times than alerts that only occurred once ( P < .001). This metric can be used in future research to evaluate the effectiveness and efficiency of interruptive prescribing alerts.